Digestive system of worker termite Coptotermes curvignathus holmgren and its chemical and cellulolytic microbial properties - Sia, Siaw Lang; King, Jie Hung; Patricia,; Ong, Kian Huat; Imran Haider Samsi,; Shahrul Razid Sarbini, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Termites are able to feed and digest wood efficiently through orchestration of host and microbial enzymes. This study was carried out to characterize the anatomy of the Coptotermes curvignathus digestive system as well as its chemistry and cellulolytic microbial properties. Coptotermes curvignathus has three main regions in their digestive system namely the foregut, midgut and hindgut. The length of foregut was the shortest and the hindgut was the longest compartment. There were seven Malpighian tubules attached at the junction between the midgut and the anterior hindgut. Based on gut metabolites analysis, uric acid was found to be the most concentrated compound in all gut compartments. Some cellulolytic microbes isolated from the C. curvignathus digestive system displayed ability to produce uric acid. The second most abundant compound was propionic acid. Other organic acids, antibiotic and antioxidant compounds such as salicylic acid, butyric acid, vancomycin hydrochloride, pyrocatechol, and quercetin were also found in the fluid of C. curvignathus. From antioxidant tests, hindgut fluid of C. curvignathus exhibited the highest antioxidant activities, followed by midgut and the foregut fluids had the lowest antioxidant activity. The result agrees with the metabolites analysis, where ascorbic acid was found mainly in hindgut. The isolation of uric acid producing microbes from the gut of C. curvignathus is quite encouraging for further cultivation-based investigations, which are important to improve our understanding of the functional interactions of the symbiotic microbes involved in the digestion of wood matter in termites.